Impactos regionais de crises financeiras: estudo sobre as respostas dos estados brasileiros à crise financeira global - Igor Santos Tupy (2015)
This dissertation aims to analyze the regional transmission of the 2008 financial crisis effects on Brazilian regional economies and their responses to this shock. Specifically, the work concerns about the differentiated patterns of responses of the Brazils twenty-seven States to this global event that contributed to lead Brazilian Economy to a recession on the last quarter of 2008. In this context, the reappearance of the regional question on economic debates about impacts of the crisis is theoretically reinforced, mainly by highlighting the emergence of the notion of regional economic resilience as a useful tool to understand the uneven patterns by which local and regional economic systems respond and react to recessive shocks. Additionally, the references of the dissertation include some elements of Post-Keynesian Theory applied to regional context such as differentiated liquidity preference across territory and its effects during crises in order to discuss the role of credit constraints on this process. Decreases on credit and exports werepointed as the main transmitters of international crisis to the national economy during 2008. In this sense, this study evaluates how this channels could be responsible to differentiated impacts among Brazilian states. The regional responses to shocks in transmission channels were simulated by a Vector Autoregressive Model (VAR) and their Impulse Response Functions. In a counterfactual exercise, we examined how these simulated responses have fitted to real regional frame of crisis impacts. Further, the uneven patterns of state economic activity resistance to and recovery from recession were analyzed by twoindicators Sensitivity Index and Recovery Index and by a Resilience Equation estimated by Seemingly Unrelated Regressions (SUR model). It was verified that a common recessive shock, in the financial crisis period, causes heterogeneous impacts on Brazilian States. Such differences occurred in extent, timing and duration both in the regional responses to transmission channels shocks and in the resistance and recovery analysis. In general lines, results had indicated that the external insertion and the linkages with foreign markets were the main factorresponsible by the differentiated impacts of subprime crisis across Brazilian states. Indeed, most affected states were those that are most dependents of exports, mainly those specialized on mining industry, metallurgy and some commodities(i.e. Minas Gerais and Pará). Analysis allowed to indicate the strong impact on an industrial district (Manaus), reflecting on the results of Amazonas state. Furthermore, on the Brazilian Federal District case was verified the high resistance and low recovery that shows the stability of employment in public sector on this locality. Finally, credit constraints have shown higher, more intense and widespread potential to transmit regionally the recessive crisis effects than the decreases of exportation. However, it seems that countercyclical policies adopted by the central government may had reduced their effective impacts over Brazilian non-core states such as the Northeast region. Instead, these states could be potentially most affected by a credit decrease were most resistant to the crisis. The reestablishing of the credit market liquidity by the Brazilian government was an important tool to recover from financial crises.